Historical Perspective of Pore-Forming Activity Studies of Voltage-Dependent Anion Channel (Eukaryotic or Mitochondrial Porin) Since Its Discovery in the 70th of the Last Century - Benz, Roland (Frontiers in Physiology, 2021)
Eukaryotic porins, also known as VDACs (Voltage-Dependent Anion Channel) are the most frequent protein in the outer membrane of mitochondria that are responsible for cellular respiration. Mitochondria are most likely descendants of strictly aerobic Gram-negative bacteria from the α-proteobacterial lineage. In accordance with the presumed ancestor, mitochondria are surrounded by two membranes. The mitochondrial outer membrane contains besides the eukaryotic porins responsible for its permeability properties and a variety of other functions also the TOM apparatus responsible for the uptake of many mitochondrial proteins that are encoded in the nucleus and synthesized in the cytoplasm. The recognition and the study of electrophysiological properties of eukaryotic porin or VDAC started in the late seventies of the last century by a study of Schein et al., who reconstituted the pore from crude extracts of Paramecium mitochondria into planar lipid bilayer membranes (Schein et al., (1976) J Membr Biol. 30(2), 99-120.). Whereas the literature about structure and function of eukaryotic porins was comparatively rare during the first ten years after the first study, the number of publications started to explode with the first sequencing of human Porin 31HL and the recognition of the important function of eukaryotic porins in mitochondrial metabolism. Many genomes contain more than one gene coding for homologs of eukaryotic porins. More than one hundred sequences of eukaryotic porins are known to date. Although the sequence identity between them is relatively low, the polypeptide length and in particular, the electrophysiological characteristics are highly preserved. This means that all eukaryotic porins studied to date are anion selective in the open state. They are voltage-dependent and switch into cation-selective substates at voltages in the physiological relevant range. A major breakthrough was also the elucidation of the 3D-structure of the eukaryotic pore, which is formed by nineteen β-strands similar to those of bacterial porin channels. The function of the presumed gate, an α-helical stretch of twenty amino acids allowed further studies with respect to voltage-dependence and function, but its exact role in channel gating is still not fully understood.